Differential Participation of Endothelin Receptors in Estradiol-Induced Oviductal Egg Transport Acceleration in Unmated and Mated Rats - Cardenas-Sankan, G; Orihuela-Diaz, P (Elsevier (Singapore) Pte Ltd, 2012)
Objective: To determine the role of endothelin (EDN) signaling in the estradiol (E2) nongenomic and genomic mechanism that regulates egg transport in the oviduct. Methods: The effect of the selective agonists of ETA (BQ610) or ETB (BQ788) on the E2-induced egg transport acceleration in unmated and mated rats was compared. Then, the level and distribution of ETA or ETB in the oviduct of unmated and mated rats following E2 treatment was analyzed. Finally, the effect of E2 on the oviductal release of EDN1 in unmated and mated rats was determined. Results: The intraoviductal E2 nongenomic pathway required participation of ETA and ETB while the E2 genomic pathway required only ETA. Furthermore, expression of ETA and ETB was present in the oviduct although their levels were similar between unmated and mated rats and following E2 treatment. On other hand, both EDN receptors were differentially localized in the oviductal cells where ETA was mainly localized in the apical zone of epithelial cells and in the stroma and muscle while ETB was localized exclusively in the apical zone of the epithelium. However, mating and E2 treatment did not affect the localization of these receptors in the oviductal cells. Conclusions: These results indicate that mating influences the role of EDN signaling in the effect of E2 on egg transport in the rat oviduct. This effect of mating on EDN signaling is not explained by a change in the expression or localization of their receptors along the oviduct. These findings provides the first evidence of an association between mating and EDN in order to modulate a physiological process regulated by E2 in the mammalian oviduct. © 2012 Hainan Medical College.